2012
DOI: 10.1002/cae.20407
|View full text |Cite
|
Sign up to set email alerts
|

An integrated electrical drive control laboratory: Speed control of induction motors

Abstract: This paper presents an integrated environment for speed control of vector controlled induction motor (IM) including simulation and experimental study. In the prepared integrated environment, students and researchers can realise the speed control of IM by selecting the classical controllers such as proportional þ integral þ derivative (PID) and integral þ proportional (IP) or intelligent controllers such as fuzzy (FC), neural network (NNC) and neuro-fuzzy (NFC). Users can perform simulation and experimental stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The most important element of the control system is a controller. Personal computers (PCs) connected to data acquisition (DAQ) cards [8]- [11], compact proportional-integral-derivative (PID) control devices [12], programmable logic controllers (PLCs) [13], [14], microcontrollers (μCs) [6], [15], [16] and digital signal processors (DSPs) [17] are the most commonly used controllers in practically all industrial control applications. These controllers interconnect all parts of the physical and non-physical of a system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important element of the control system is a controller. Personal computers (PCs) connected to data acquisition (DAQ) cards [8]- [11], compact proportional-integral-derivative (PID) control devices [12], programmable logic controllers (PLCs) [13], [14], microcontrollers (μCs) [6], [15], [16] and digital signal processors (DSPs) [17] are the most commonly used controllers in practically all industrial control applications. These controllers interconnect all parts of the physical and non-physical of a system.…”
Section: Introductionmentioning
confidence: 99%
“…Ekici [10] conducted a study on the computer-assisted training method for power analysis courses. Dandil [17] realized a simulation and application study on an induction motor control for undergraduate students. A study conducted by Shyr [26] revealed that the project-based mechatronics learning is more effective in the learning of undergraduate students.…”
Section: Introductionmentioning
confidence: 99%